Hi everyone,

I found this limit in a research paper, and I'm simply not able to get to the same result.
I hope some of you can help me a little bit.
Hypothesis from the paper:
 \lim_{\beta \rightarrow 0} \frac{1}{\alpha} (C^{\beta}+\theta L^{Beta})^{\frac{\alpha}{\beta}} = \frac{1}{\alpha}(C^{\frac{1}{1+\theta}}+\theta L^{\frac{\theta}{1 + \theta}})^{\alpha}
My idea so far, was to take the logarithm of the problem, and then use some de l'H˘pital:
\lim_{\beta \rightarrow 0} \frac{1}{\alpha} (C^{\beta}+\theta L^{Beta})^{\frac{\alpha}{\beta}} = e^{\left(  \lim_{\beta \rightarrow 0} log\left(\frac{1}{\alpha} (C^{\beta}+\theta L^{Beta})^{\frac{\alpha}{\beta}}\right) \right)}
\lim_{\beta \rightarrow 0} log\left(\frac{1}{\alpha} (C^{\beta}+\theta L^{Beta})^{\frac{\alpha}{\beta}}\right) = \lim_{\beta \rightarrow 0}   \frac{log(1+\theta)}{\beta}  + \lim_{\beta \rightarrow 0} \frac{(\frac{1}{(1+\theta)}K^{\beta} + \frac{\theta}{(1+\theta)} L^{beta})}{\beta}
Using de l'H˘pital on the second term yields:
= \lim_{\beta \rightarrow 0}   \frac{log(1+\theta)}{\beta}  + \frac{1}{1+\theta} log(K) + \frac{\theta}{1+\theta}log(L)
As you can see, the first term is divergent, which should mean that the limit doesn't exist.
What do you think ?
Is the paper wrong? Am I wrong ?

Thanks a lot in advance

El Botas